Alimentación, factores socioeconómicos, crecimiento y desarrollo psicomotor en niños de la I.E.I. Victoria Barcia Boniffatti, Iquitos. 2023 - Cordova Rodriguez, Cristina Stephanie (2024)
Objectives: Determine the relationship of socioeconomic factors and nutrition with growth and psychomotor development in children of the I.E. Initial Victoria Barcia Boniffatti, Iquitos, 2023. Methods: Observational study and cross-sectional design, which adopts a prospective perspective in planning data collection. Results: Maternal age showed a significant relationship with off-target psychomotor development, with an aOR of 0.906 (95% CI: 0.855–0.959; p = 0.001). The NutriSTEP variable, which indicates nutritional risk, was associated with off-target psychomotor development, although the association did not reach statistical significance (aOR: 0.939; 95% CI: 0.868–1.017; p = 0.078). Childhood growth is significantly associated with inadequate growth and off-target psychomotor development (p = 0.049). Children with inadequate growth were 1.9 times more likely (95% CI: 1.003–4.008) to develop problems in psychomotor development compared to those with adequate growth. Furthermore, nutritional risk and inadequate growth were shown to correlate with increased risk of off-target psychomotor development. Conclusions: It is concluded that maternal age and inadequate child growth are significantly associated with off-target psychomotor development. Children with inadequate growth were almost twice as likely to experience problems in psychomotor development. Socioeconomic characteristics and childhood diet were also correlated with an increased risk of off-track psychomotor development.